PRODUKTIVITAS LAHAN DAN NKL PADA TUMPANGSARI TIGA VARIETAS JAGUNG PULUT (Zea mays caratina Kulesh) DENGAN BERBAGAI INTERVAL WAKTU TANAM KACANG TANAH (Archis hipogaea L.) SEBAGAI TANAMAN SELA - Kristono Yohanes Fowo (AGRICA, 2017)
Land Productivity and NKL on Tumpangsari Three Maize Variety Cultivation (Zea mays caratina Kulesh) With Various Interval Time Plants (Archis hipogaea L.) as Select Plant. This study aims to determine the combination of timing planting and planting techniques that can improve the productivity of land and NKL values ??on the application of intercropping cultivation technology in dry land conditions in Ende-NTT. The experimental design using Division Split Plot (RPT) consists of two factors repeated three times. The treatment of corn varieties (V1: Local varieties, V2: Uri varieties, V3: Binthe Pulu varieties) while planting time was placed as subplot (T1: Maize planted 15 days after peanut planting T2: Corn is grown together with peanut planting T3: Corn is grown 15 days before planting peanuts, as comparison of each treatment is also planted in monculture, so that obtained 31 units of experiment plot The data collection is done by calculating dry weight of seeds produced by all plant crops in the harvest plots, and the crops in the harvest plots. The results show that intercropping crops between pulut and peanut crops in various pulses maize varieties and peanut planting times increased the productivity of the land 1, with the highest land productivity dida The maize varieties of Uri corn is grown simultaneously with groundnut planting (V2T2) of 1.52 and followed by treatment of local varieties of pulutans planted together with peanut plant (V1T2) of 1.46.